(untitled) (Journal of Engineering, 2013)
The performance of a solar assisted desiccant cooling system for a meeting-hall located in the College of Engineering/University of Baghdad was evaluated theoretically. The system was composed of four components; a solar air heater, a desiccant dehumidifier, a heat exchanger and an evaporative cooler. A computer simulation was developed by using MATLAB to assess the effect of various design and operating conditions on the performance of the system and its components. The actual weather data on recommended days were used to assess the load variation and the system performance during those days. The radiant time series method (RTS) was used to evaluate the hourly variation of the cooling load. Four operation modes were employed for performance evaluation. A 100 % ventilation mode and 3 recirculation modes, 30 % , 60 % and 100 % recirculation of room air. The concept of variable air volume was employed as a control strategy over the day, by changing the supply airflow rate to match the variation in the cooling load. The results showed that the reduction in moisture content at regeneration temperatures from 55 o C to 75 o C lead to adequate removal of the high latent load in the meeting-hall. Also, the 30 % recirculation of return air resulted in comfortable indoor conditions satisfying the ventilation requirements for most periods of system operation. In addition, the COP of the system was high compared with the conventional vapor compression system. It varied from 1 to 13, when considering solar energy used to regenerate the desiccant material as free energy.